Persoalan Dasar dalam Dialog Injil dan Kebudayaan: Integrasi Teologi Akademik dan Teologi Jemaat dalam Diskusi Lintas Sinodal mengenai Teologi Kontekstual dan Kebutuhan Hermeneutik Multikultural di Gereja Masehi Injili Timor dan Gereja Toraja Mamasa - Ronal Arulangi (Akoloutheo: Jurnal Pengabdian Kepada Masyarakat, 2026)
This paper is a result of research and community service that integrates academic theological studies with the church's need for theological principles to examine the relationship between church theology and local culture at the practical level in congregational ministry. It explores the practical theological experiences of the Gereja Masehi Injili di Timor (GMIT) and the Gereja Toraja Mamasa (GTM) in conjunction with academic theological studies. An inadequate understanding of contextualization is considered to be the cause of the lack of development of relevant methods and approaches at the practical level in congregations by church ministers. The discussion, revealed that the primary issue that needs to be addressed is resolving issues of terminology and dogmatics presumption. Using a qualitative analysis method, this study confirms initial needs and can provide suggestions for a methodological design to fulfill the objectives of a future church framework on the contextualization of theology and dialogue between the gospel and culture, particularly in local church organizations with ethnic backgrounds such as both churches. It also reveals the need for an adequate hermeneutic method to ensure the application of scientific principles and practical needs that emphasize dialogue in four contexts.